1998
DOI: 10.1177/002246699803200303
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Education Programs in Resource and Inclusive Settings

Abstract: In this study, Individualized Education Programs (lEPs) for students in resource and inclusive settings were compared. Participants were 108 students with mild disabilities (50 in resource settings and 58 in inclusive settings) in Grades 1 through 6 with lEPs in reading. lEPs for students in resource programs had more service minutes, more long-range goals, and used more sources of information than IEPs for students in inclusive programs. Furthermore, there was a better concordance between IEP components and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 12 publications
2
26
0
1
Order By: Relevance
“…The research indicates that schools continue to struggle with the basic procedural and substantive requirements of IEPs (Drasgow et al, 2001;Etscheidt, 2003), including components related to secondary transition planning (Landmark & Zhang, 2013;Shearin et al, 1999). In addition, multiple studies (Agran et al, 2002;Espin et al, 1998;Kwon et al, 2011;Mattie & Kozen, 2007;Millar, 2009;Ruble et al, 2010) reported findings that raised concerns regarding IEP content, including the quality of IEP goals and objectives and the extent to which the goals facilitated access to the general education curriculum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research indicates that schools continue to struggle with the basic procedural and substantive requirements of IEPs (Drasgow et al, 2001;Etscheidt, 2003), including components related to secondary transition planning (Landmark & Zhang, 2013;Shearin et al, 1999). In addition, multiple studies (Agran et al, 2002;Espin et al, 1998;Kwon et al, 2011;Mattie & Kozen, 2007;Millar, 2009;Ruble et al, 2010) reported findings that raised concerns regarding IEP content, including the quality of IEP goals and objectives and the extent to which the goals facilitated access to the general education curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the authors of these studies presented findings that identified problems with the extent to which instructional supports, services, and IEP goals were appropriate to ensure student participation in the general education program (Agran et al, 2002;Kurth & Mastergeorge, 2010;Ruble et al, 2010), support peer-interactions (Gelzheiser et al, 1998;Kwon et al, 2011), and address behavioral supports (Mattie & Kozen, 2007). There were also findings that raised concerns about the extent to which IEP content was individualized based on student needs (Espin et al, 1998), and adequately addressed transitionrelated needs (Millar, 2009).…”
Section: Iep Contentmentioning
confidence: 99%
“…They conclude that if the child is better served in the resource room, it is the legal responsibility under LRE to place him there. Espin, Deno, and Albayrak-Kaymak, (1998) reported that IEPs for students with disabilities in a resource room included more individualized instruction, long-range goals and service minutes than students serviced in inclusive settings. According to a study on inclusion by Idol (2006), many teachers still prefer using the resource room and consider it the only way to help some students with disabilities.…”
Section: Types Of Service and Placement Optionsmentioning
confidence: 99%
“…In the European educational context, however, the cultural background of pupils has not been a significant issue, unlike in the United States, where minority pupils have been highly overrepresented in special education programmes over the decades (Artiles & Trent, 1994;Hosp & Reschly, 2004). In the 1960s, however, serious doubts began to be raised about the rationale for separate special education (see, for example, Dunn, 1968), and this debate has continued ever since (see, for example, Fuchs & Fuchs, 1995;Mastropieri & Scruggs, 1997;Espin et al, 1998;Powell, 2009;Zigmond et al, 2009). In their review of distinctive pedagogies based on discreet categories of educational needs, Norwich & Lewis (2001) came to the conclusion that such pedagogies may not even exist.…”
Section: Introductionmentioning
confidence: 99%